International Society for Technology in Education (ISTE) Standards For EFL Students as 21st Century Skills - Marwa, Marwa; Wahyudi Saputra; Herlinawati, Herlinawati (Universitas Lancang Kuning, 2024)
This survey research aimed at investigating International Society for Technology in Education (ISTE) Standards of EFL Students in an English Education Department at a university in Pekanbaru, Riau. The method used was descriptive quantitative which involved 121 samples. The samples were selected by using random sampling technique from third, fifth, and seventh semesters. The questionnaire adopted from Hazamayeh (2021) used as the main instrument to collect the data. The data was analyzed by using descriptive statistics (the sum of score, mean and standard deviation) which then interpreted descriptively. The study revealed that the students’ mean of ISTE Standards reached 3.92 which was categorized into a Moderate level. It was measured by calculating the avarage score of the ISTE six indicators namely Creativity and Innovation; Communication and Collaboration; Research and Information Fluency; Critical Thinking, Problem Solving and Decision Making; Digital Citizenship; and Technology Operations and Concepts. This “Moderate” level indicates that the EFL students are still in on going process to maximize their ability to use technology as a means of learning.